Cervical Cancer among Women Attending a Tertiary Care Hospital in Perambalur, India - Dandekar, R. H.; Varadheswari, .; Sharanya , . (Current Practice in Medical Science Vol. 7, 2022)
The present study was conducted to estimate the prevalence of cervical cancer among women attending a tertiary care hospital. Also it revealed their knowledge, attitude and practice regarding cervical cancer. Cervical cancer prevalence can be decreased by having a positive attitude toward premalignant cervical lesion screening. The study population consisted of 74 women who were OBG patients at a tertiary care hospital in Perambalur. To determine the prevalence, Pap smear tests were administered to all the women. To evaluate the women's knowledge, attitudes, and practices surrounding cervical cancer, a questionnaire was created and interviews were conducted with them. The participants' attitudes regarding cervical cancer screening were favourable in 83.78 percent of cases. Most participants weren't getting their cervical cancer checked. Only 1.35% was found to have good screening practice on cervical cancer with 1.35% of the women having irregular. The study found that although half of the women participants had some level of knowledge about cervical cancer, the community had a very low screening rate.